1298 THE IMPACT OF ACUTE HEALTHCARE UTILISATION ON FUNCTIONAL DECLINE IN OLDER ADULTS OVER TIME: A POPULATION-BASED COHORT STUDY. (16th January 2023) - Conneely, M; Leahy, S; Trépel, D; Robinson, K; Boland, F; Moriarty, F; Galvin, R
Abstract: Introduction: Acute healthcare use varies by age, with older adults the highest users of most acute healthcare services. International reports have highlighted increased use of Emergency Department (ED) services by older adults. Older adults who visit the ED may be admitted to hospital or discharged home and are vulnerable to adverse outcomes including cognitive decline, falls, readmission, mortality and hospital acquired limitations in activities of daily living. Using data from The Irish Longitudinal Study on Ageing (TILDA), the aim of this study was to investigate the impact of acute healthcare utilisation at baseline on subjective and objective measures of function at four-year follow-up in older adults. Methods: This study represents a secondary analysis of a prospective cohort study where data from Wave 1 (baseline) and Wave 3 (four-year follow up) of TILDA were analysed in conjunction with a public and patient involvement group of older adults. Acute healthcare utilisation was defined as an ED visit with or without hospitalisation in the previous 12 months. Function was assessed objectively using Timed-Up-and Go (TUG) and grip strength and subjectively using self-report limitations in activities of daily living and instrumental activities of daily living. Results: A total of 1516 participants met the study inclusion criteria. Mean age was 70.9 years (SD=4.6) and 48% were male. At baseline, 1280 participants reported no acute healthcare use. 118 indicated an ED visit but no hospitalisation in the previous twelve months and 118 reported both an ED visit and hospitalisation. Adjusting for all covariates, compared to those with no acute healthcare utilisation, those with an ED visit with no hospital admission had poorer TUG performance at follow up (β= 0.67, 95% CI: 0.34, 1.29, p=0.039). Conclusion: The results of this study support a relationship between acute healthcare utilisation and functional decline assessed by TUG at follow-up.